The Roles of Elected Representatives in Political Parties: What’s the Challenges? - Brahim, Malike (Canadian Center of Science and Education, 2017)
The elected representatives have important roles that involved parliamentary and constituency roles, social services, and to political party.They need to split their time between working in legislative, in constituency and for the party.In Malaysia, elected representatives have important roles in party to affiliate party apparatus, carry out election campaigns, and try to convince voting citizen by casting their ballot for them.The research finding indicated that the parties are due in part to competition for party positions, thus will create money politics and leadership conflicts.Finally, few elected representative hopping to oppose party.